On Generalized Caristi Type Satisfying Admissibility Mappings. (23rd January 2023) - Almazah, Mohammed M. A.; Hardan, Basel; Hamoud, Ahmed A.; Ali, Faisal A. M.
Abstract : In this article, the existence and uniqueness of a fixed point were investigated using the concept of σ, γ -contractive in the context of Hausdorff metric space. A well-known Caristi type is primarily generalized by the new results. The result is improved by building up an example.